2022
DOI: 10.3390/foods11060823
|View full text |Cite
|
Sign up to set email alerts
|

A Voting-Based Ensemble Deep Learning Method Focused on Multi-Step Prediction of Food Safety Risk Levels: Applications in Hazard Analysis of Heavy Metals in Grain Processing Products

Abstract: Grain processing products constitute an essential component of the human diet and are among the main sources of heavy metal intake. Therefore, a systematic assessment of risk factors and early-warning systems are vital to control heavy metal hazards in grain processing products. In this study, we established a risk assessment model to systematically analyze heavy metal hazards and combined the model with the K-means++ algorithm to perform risk level classification. We then employed deep learning models to cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Remarkably, several studies have demonstrated the high level of accuracy of the machine learning methods [67][68][69][70], and they used these models for improving many problems. On the other hand, From the literature, most of the studies have investigated the relationship between oil prices and macroeconomic factors, but such studies seldom focus to validate the agreement on how much these macroeconomic factors influence oil prices [71].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remarkably, several studies have demonstrated the high level of accuracy of the machine learning methods [67][68][69][70], and they used these models for improving many problems. On the other hand, From the literature, most of the studies have investigated the relationship between oil prices and macroeconomic factors, but such studies seldom focus to validate the agreement on how much these macroeconomic factors influence oil prices [71].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Geng et al propose both [ 25 , 26 ] used the AHP-EW algorithm to generate a combined risk value for each sample and then combined it with a machine learning model for risk prediction. On this basis, Wang et al [ 27 ] used integrated learning techniques to improve the accuracy of the prediction models. However, existing research methods require the introduction of external expert knowledge, slow convergence, or preprocessing of food data to calculate the desired output of the model.…”
Section: Related Workmentioning
confidence: 99%
“…Quantitative assessment methods are data-driven models [ 9 ]. They are based on data to establish a mathematical model and use the mathematical model to calculate the risk value of the index [ 10 ]; these models include the random forest algorithm [ 11 ], support vector machine (SVM) [ 12 ], and back-propagation (BP) network [ 13 ].…”
Section: Introductionmentioning
confidence: 99%